2006
DOI: 10.1016/j.febslet.2006.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the [NiFe]‐hydrogenase maturation protein HypD

Abstract: A mutational screen of amino acid residues of hydrogenase maturation protein HypD from Escherichia coli disclosed that seven conserved cysteine residues located in three different motifs in HypD are essential. Evidence is presented for potential functions of these motifs in the maturation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 26 publications
10
77
3
Order By: Relevance
“…It was previously suggested [5,15,17] that a nucleophilic iron acts as the acceptor for the cyanide ligand generated by the HypFE maturases. Here we have demonstrated that the anaerobically purified HypC Strep -HypD complex carries not only two CN À ligands but also coordinates a single CO.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was previously suggested [5,15,17] that a nucleophilic iron acts as the acceptor for the cyanide ligand generated by the HypFE maturases. Here we have demonstrated that the anaerobically purified HypC Strep -HypD complex carries not only two CN À ligands but also coordinates a single CO.…”
Section: Discussionmentioning
confidence: 99%
“…1B). Two highly conserved motifs (motif 1: C 41 -G-X-H 44 -X-H and motif 2: G-P-G-C 69 -P 70 -V 71 -C 72 -X-X-P 75 ) within HypD have been shown to be essential for hydrogenase maturation [17] and it is conceivable that the two additional Fe ions are coordinated by these motifs.…”
Section: Identification Of Cn à and Co Ligands In The Hypcd Complexmentioning
confidence: 99%
See 3 more Smart Citations